Developing a play-anywhere handheld AR storytelling app using remote data collection - Raeburn, Gideon; Welton, Martin; Tokarchuk, Laurissa (Frontiers in Computer Science, 2022)
Immersive story experiences like immersive theater productions and escape rooms have grown in popularity in recent years, offering the audience a more active role in the events portrayed. However, many of these activities were forced to close at the start of the COVID-19 pandemic, arising from restrictions placed on group activities and travel. This created an opportunity for a story experience that users could take part in around their local neighborhoods. Five mobile applications (apps) were developed toward this goal, aiming to make effective use of available local map data, alongside virtual content overlaid on users' surroundings through Augmented Reality (AR), to offer additional story features not present in the real environment. The first two apps investigated the feasibility of such an approach, including the remote field testing of the apps, where participants used their own devices across a variety of locations. Two follow-up apps further aimed to offer an improved user experience, also adopting a more standardized testing procedure, to better ensure each app was completed in an intended manner by those participating remotely. Participants rated their experience through immersion and engagement questionnaire factors that tested for their appropriateness to rate such experiences, in addition to providing their feedback. A final app applied the same AR story implementation to a curated site-specific study, once pandemic restrictions had eased. This combination of remote studies and subsequent curated study offered a reverse methodology to much previous research in this field, but was found to offer advantages in corroborating the results of the remote studies, and also in offering new insights to further improve such an AR story app, that is designed to be used at an outdoor location of the user's choosing. Such an app offers benefits to those who may prefer the opportunity to take part in such an activity solo or close to home, as well as for storytellers to develop an outside story for use at a variety of locations, making it available to a larger audience, without the challenges and costs in migrating it to different locations.